2006
DOI: 10.1037/1082-989x.11.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Confidence intervals and replication: Where will the next mean fall?

Abstract: Confidence intervals (CIs) give information about replication, but many researchers have misconceptions about this information. One problem is that the percentage of future replication means captured by a particular CI varies markedly, depending on where in relation to the population mean that CI falls. The authors investigated the distribution of this percentage for varsigma known and unknown, for various sample sizes, and for robust CIs. The distribution has strong negative skew: Most 95% CIs will capture ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 21 publications
3
97
1
Order By: Relevance
“…Cumming and Maillardet (2006) stated that "considering whether an effect is replicable is at the heart of drawing inferences from data" (p. 217). Furthermore, although the additivity of the Stroop effect with SOA observed by Fagot and Pashler (1992, Experiment 7) plays a crucial role in the theoretical argumentation of Dell'Acqua et al (2007), there are no reported replications of this additivity in the literature.…”
Section: The Present Studymentioning
confidence: 99%
“…Cumming and Maillardet (2006) stated that "considering whether an effect is replicable is at the heart of drawing inferences from data" (p. 217). Furthermore, although the additivity of the Stroop effect with SOA observed by Fagot and Pashler (1992, Experiment 7) plays a crucial role in the theoretical argumentation of Dell'Acqua et al (2007), there are no reported replications of this additivity in the literature.…”
Section: The Present Studymentioning
confidence: 99%
“…In 20 of the 24 cases, the 95% CI includes the mean next above it in the figure. That is 83.3% of the experiments, which happens to be very close to the longrun average of 83.4% (Cumming & Maillardet, 2006;Cumming, Williams, & Fidler, 2004). So a 95% CI is an 83% prediction interval for the ES estimate of a replication experiment.…”
Section: Replication P Values and Cismentioning
confidence: 99%
“…Because of the importance of replication probability and the confusion surrounding it, recent articles in numerous disciplines have urged researchers to consider replication probability more carefully (e.g., Cumming, 2008;Cumming & Maillardet, 2006;Gorroochurn, Hodge, Heiman, Durner, & Greenberg, 2007;Greenwald, Gonzalez, Harris, & Guthrie, 1996;Killeen, 2005;Robinson & Levin, 1997;Sohn, 1998). Researchers have been offered formulas with which to compute the probability of replicating their current results, and they have been advised to report the resulting replication probabilities as well as-or even in preference to-more traditional statistical measures (e.g., Greenwald et al, 1996;Killeen, 2005;Psychological Science editorial board, 2005).…”
mentioning
confidence: 99%